On the Occasion of Georgia's Second Anniversary of the Rose Revolution - Wolfowitz, Paul (2016)
Paul Wolfowitz, President of the World Bank, celebrated the second anniversary of the Rose Revolution in Georgia. He spoke about the evidence of reduced corruption in Georgia. Georgia had the second largest improvement in performance last year of any country in the world. In transforming its own society, Georgia sets an example for the region. He assured that Georgia can count on the World Bank Group as a committed partner. Finally, he concluded by saying that Georgian determination which shined so brightly in the Rose Revolution will continue to be a beacon supporting the Georgian ideals of freedom and prosperity.